2014
DOI: 10.1155/2014/967534
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Response Surface Methodology in the Study of Photodegraded Industrial Dairy Effluents by the Photo-Fenton Process: Optimization and Economic Viability

Abstract: This study presents results from an application of Photo-Fenton process for organic-load reduction in dairy effluents. Process efficiency was evaluated in terms of percentage dissolved organic carbon, chemical oxygen demand, and biochemical oxygen demand (DOC, COD, and BOD, resp.), whose initial values were 1658 ± 145 mg O 2 L −1 , 9500 ± 500 mg O 2 L −1 , and 2400 ± 100 mg O 2 L −1 , respectively. We applied a statistical design represented by Box-Behnken factorial design inclusive of Fenton's reagent, the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Apresentou propriedades ácidas, com a faixa de pH entre 3,5 e 4,5, e salinas, com condutividade elétrica de 2,052 μS cm -1 , características comumente encontradas em efluentes de SQ. Além disso, verificou-se que o grau de matéria orgânica recalcitrante presente no SQ na razão DBO 5 /DQO, de 0,38, dificultaria o tratamento biológico convencional de forma direta (LOURES et al, 2014)…”
Section: Coagulação/floculaçãounclassified
“…Apresentou propriedades ácidas, com a faixa de pH entre 3,5 e 4,5, e salinas, com condutividade elétrica de 2,052 μS cm -1 , características comumente encontradas em efluentes de SQ. Além disso, verificou-se que o grau de matéria orgânica recalcitrante presente no SQ na razão DBO 5 /DQO, de 0,38, dificultaria o tratamento biológico convencional de forma direta (LOURES et al, 2014)…”
Section: Coagulação/floculaçãounclassified
“…As the COD/BOD ratio is 4.2, the wastewater can be considered biodegradable only if the factors influencing the process are suitable for microbial metabolism. If the ratio is 5.0 > COD/BOD > 2.5, a proper biological process should be chosen in order to reach a desirable reduction of organic matter (LOURES et al, 2014).…”
Section: Wastewater Characterizationmentioning
confidence: 99%
“…Analysis of this dual behavior is important, given that changes in reaction conditions, such as reagent feed flow rates, may influence the process, possibly precluding radical oxidant consumption or resulting in low oxidation of carbonaceous compounds. 30 This study is aimed to compare the empirical model proposed by Siqueira and collaborators with two approaches for the investigation of leachate degradation. 28,29 The first approach is a kinetic model developed by Izaŕio Filho et al 26 and applied by Izaŕio Filho et al 27 It is based on the main kinetic equations found in the literature for AOPs and was successfully applied in the study of photo-Fenton degradation of undiluted industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…In studies on leachate treatment by AOPs, it was found that stochastic modeling allowed using all experimental data, contributing to a broader understanding of the degradation process and favoring optimization. Two distinct phases of the oxidation process were identified, a first phase occurring very rapidly and a second phase occurring at a slower rate. Analysis of this dual behavior is important, given that changes in reaction conditions, such as reagent feed flow rates, may influence the process, possibly precluding radical oxidant consumption or resulting in low oxidation of carbonaceous compounds …”
Section: Introductionmentioning
confidence: 99%